Gauchon, Pascal i Huissoud, Jean-Marc (coord.) (2009): Les 100 Lieux de la Géopolitique - Ferrer Gallardo, Xavier (Documents d’Anàlisi Geogràfica, 2012)
Gauchon, Pascal i Huissoud, Jean-Marc (coord.) (2009) Les 100 Lieux de la Géopolitique París: Presses Universitaires de France, 128 p. ISBN: 9782130583448